2020
DOI: 10.1186/s43045-020-0015-6
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and health-seeking behavior among family caregivers of mentally ill patients at Assiut University Hospitals: a cross-sectional study

Abstract: Background: Mental illness is associated with misunderstanding and unfavorable attitude worldwide. The belief in its spiritual nature made traditional healers the main service consultants for mentally ill patients. The present study is a cross-sectional study conducted among 425 main family caregivers of mentally ill patients at Assiut University Hospital. The objective of the study was to assess the caregivers' knowledge and attitude towards mental illness as well as their health-seeking behavior for their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
4
11
1
2
Order By: Relevance
“…The result of the current study revealed that there is a highly significant relationship between caregivers' level of knowledge and their age that older caregivers had a low level of knowledge satisfactory than younger caregivers. This is consistent with the findings of (72) in their study conducted in in Egypt reported that the caregivers' age was related to their level of knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result of the current study revealed that there is a highly significant relationship between caregivers' level of knowledge and their age that older caregivers had a low level of knowledge satisfactory than younger caregivers. This is consistent with the findings of (72) in their study conducted in in Egypt reported that the caregivers' age was related to their level of knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…There is no difference in knowledge levels between caregivers who live in rural areas and those who live in towns and cities because caregivers can obtain knowledge and information about their patients' diseases regardless of where they live. This is consistent with the findings of the study conducted in Egypt by (72) who claimed that caregivers' residence place was unrelated to their knowledge of their patients' diseases and illness.…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that positive parents' attitude toward mental was associated with a higher educational level. This comes in accordance with other studies highlighting a positive relationship between the educational level and the attitude toward mental health [44]. In the Arab world, where the majority has a negative portrayal of mental disease [45], education could play a vital role in changing how people perceive mental health.…”
Section: Discussionsupporting
confidence: 91%
“…A paucity of widescale surveys reports the prevalence of depression in the Egyptian population, especially among married women in upper Egypt. This is might due to cultural variables that impede the identification and treatment of depression, including younger marriage age, especially in rural regions [30], insufficient mental health care, illiteracy, early school dropout, unemployment, and the stigma of psychiatric diseases [31][32][33].…”
Section: Introductionmentioning
confidence: 99%